2021
DOI: 10.3946/kjme.2021.193
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the structural relationships between medical students’ motivational regulation, cognitive learning, and academic performance in online learning

Abstract: Purpose The purpose of this study was to investigate the effect of motivational regulation strategies (MRSs) on cognitive learning and academic performance. Methods The participants were a total of 510 pre-medical and medical students. Survey instruments assessed the use of MRSs and cognitive learning strategies. Students’ grade point averages were used for academic performance. Structural equation modeling was used to analyze data, using Mplus ver. 7.4 (Muthén & Muthén… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
(50 reference statements)
0
12
0
1
Order By: Relevance
“… To evaluate the potential impact of the transition to distance learning on examination performance among second-year preclinical medical students at the University of Illinois Peoria School of Medicine (UICOMP) by comparing summative assessment data for medical neuroscience courses over a 2-year period (2019 and 2020), Single Medical School Undergraduate 65 Video conferencing Summative scores There is no difference in the summative value of neuroscience courses between 2019 students and 2020 students Saberi et al, 21 2021, Bahrain, Cross-sectional Study. This study investigated COVID-19 anxiety, burnout, and academic achievement in stagers and interns of Guilan University of Medical Science Single Medical School Undergraduate 138 Corona Disease Anxiety Scale (CDAS) in 2019 to measure the anxiety of COVID- 19 and Maslach Burnout Inventory-Student Survey (MBI-SS) to measure burnout GPA GPA was not significantly correlated with CDAS and MBI-SS H. Yun et al, 22 2021, South Korea, Cross-sectional Study. To investigate the effect of motivational regulation strategies (MRSs) on cognitive learning and academic performance Single Medical School Undergraduate 510 Motivational regulation strategies (MRSs) on cognitive learning GPA MRSs were highly influential to predicting students’ cognitive learning which affects their better learning performance Alkalash, 23 2022, Saudi Arabia, Cross-sectional Study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… To evaluate the potential impact of the transition to distance learning on examination performance among second-year preclinical medical students at the University of Illinois Peoria School of Medicine (UICOMP) by comparing summative assessment data for medical neuroscience courses over a 2-year period (2019 and 2020), Single Medical School Undergraduate 65 Video conferencing Summative scores There is no difference in the summative value of neuroscience courses between 2019 students and 2020 students Saberi et al, 21 2021, Bahrain, Cross-sectional Study. This study investigated COVID-19 anxiety, burnout, and academic achievement in stagers and interns of Guilan University of Medical Science Single Medical School Undergraduate 138 Corona Disease Anxiety Scale (CDAS) in 2019 to measure the anxiety of COVID- 19 and Maslach Burnout Inventory-Student Survey (MBI-SS) to measure burnout GPA GPA was not significantly correlated with CDAS and MBI-SS H. Yun et al, 22 2021, South Korea, Cross-sectional Study. To investigate the effect of motivational regulation strategies (MRSs) on cognitive learning and academic performance Single Medical School Undergraduate 510 Motivational regulation strategies (MRSs) on cognitive learning GPA MRSs were highly influential to predicting students’ cognitive learning which affects their better learning performance Alkalash, 23 2022, Saudi Arabia, Cross-sectional Study.…”
Section: Resultsmentioning
confidence: 99%
“…We divided these factors into internal and external factors. We found nine studies examining students’ internal factors that influence students’ performance such as sleep quality, 23 motivation, 22 anxiety, 19 , 21 stress, 27 , 34 students’ attitude toward online classes, 18 , 25 e-learning style, 18 and level of persistence students. 24 Most studies (n=8) showed a positive and significant correlation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] En adición, la teoría de la autodeterminación relaciona la motivación extrínseca con los tipos de regulación externa, introyectada, identificada e integrada, y la motivación intrínseca con el tipo de regulación interna.³ Según el libro Motivation and personality de Abraham H. Maslow, la motivación es la necesidad de la persona para satisfacer sus necesidades básicas, y una de ellas es el aprendizaje.⁴ La motivación es percibida como un factor crucial para mejorar el aprendizaje, por ello, los investigadores se han centrado rigurosamente en los comportamientos motivacionales y cognitivos de los estudiantes, con la finalidad de comprender plenamente el proceso de aprendizaje y mejorar el rendimiento académico, lo que constituye un área indispensable en el campo de la educación de las escuelas profesionales de la salud. 1,5 Además, dentro de la motivación podemos definir a la motivación intrínseca como aquella que ejecuta una actividad por voluntad propia para generar una satisfacción personal; en contraste, la motivación extrínseca es aquella que realiza dicha actividad como un intermediario para una recompensa o castigo; es decir, es el comportamiento humano controlado por medidas externas.…”
Section: Introductionunclassified